MO674: Risk Factors for Abdominal Wall Hernias in Peritoneal Dialysis Patients. (3rd May 2022) - Alferes, Daniela; Almeida, Catarina; Carmo, Rute; Lopes, Daniela; Carlos Fernandes, João; Marta Gomes, Ana; Clara Almeida, Maria
Abstract: BACKGROUND AND AIMS: Abdominal hernias are relatively common non-infectious complications in peritoneal dialysis (PD) patients with reported prevalence rates ranging from 7% to 27.5%. This complication can be troublesome and is sometimes associated with PD suspension and transition to hemodialysis, that can be transiently or definitively. Several risk factors for hernia formation have been proposed and included male gender, advanced age, autosomal dominant polycystic kidney disease (ADPK) and previous hernia repair. A larger dialysate diffusion volume is associated with increased intra-abdominal pressure and has been reported to increase the risk of hernia. However, studies are in conflict regarding risk factors for hernia formation. The aim of this study was to establish the incidence and the risk factors for hernia formation in patients receiving PD at our center. METHOD: We developed a single-center, retrospective, observational study. Incident PD patients from January 2010 until October 2020 were screened for inclusion. Multiple logistic regression based on variables with P- value <0.05 in univariate comparative test and Cox regression were applied to estimate the predictors for hernia formation. A value of P < 0.05 was considered statistically significant. RESULTS: A total of 163 PD patients were enrolled since and followed until December 2020, with 53 hernia events and 32 hernioplasties being registered in 28 patients (52.8%). The incidence rate was 0.09 hernias/patient/year. Table 1 summarizes the general characteristics of the patient with and without hernias. The umbilical hernias were the most common hernia type encountered (64.2%), followed by inguinal and incisional hernias. Median duration on PD therapy was 24.0 months (range: 18.5–35 months) and the median time from the start of PD to the development of hernia was 12.8 months (range: 6.1–18.9 months). The majority of patients who developed hernia were on continuous ambulatory PD (CAPD) (79.2%; n  = 42). In the univariate comparative test (Table 1 ), previous abdominal surgery (49.1% versus 11.8%, P < 0.001) and past history of hernia (34% versus 5.5%, P < 0.001) were identified as risk factors. We also observed significant differences between groups in relation to total dialysate fill-volume ( P  = 0.001) and PD modality ( P  = 0.026). There was no statistically significant difference in demographic characteristics and comorbidities. Multivariate analysis showed ADPK as the only independent risk factor for development of hernia (OR 0.2, 95% CI [0.04–1.07]). In Cox regression analysis, male gender, history of nephrectomy or other abdominal surgery, CAPD and largest total dialysate fill-volume were associated with an earlier development of hernias (P < 0.05), but no association was found with these variables in the adjusted models for the Cox regression analyses. Overall, 32 hernias (60.4%) were surgically repaired, nearly all were handled electively (29 of 32, 90.6%); the remaining 3 hernias required emergency surgery. Six hernias (18.8%) recurred, with a median time to recurrence of 13.1 months (range: 3.7–29.6 months). Longer PD vintage was the only factor associated with the recurrence of hernia ( P  = 0.005). CONCLUSION: In our study, abdominal hernias are very frequent in the PD population. ADPK was an independent risk factor for their development. We found that longer PD vintage is an important factor for recurrence of hernia after surgical repair.